2003
DOI: 10.1080/0267152032000048550
|View full text |Cite
|
Sign up to set email alerts
|

Performance-related pay: the views and experiences of 1,000 primary and secondary head teachers

Abstract: This is the first of two papers describing a study of the introduction of performance-related pay into the teaching profession in the United Kingdom. It reports the views and experiences of a national random sample of 1,000 primary and secondary head teachers in over 150 local education authorities in England who were responsible for implementing one strand of the government's performance-related pay scheme, Threshold Assessment. The second paper describes the views and experiences of teachers who were unsucce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…It is this difference that we capture here, so our results may underestimate the effect of the scheme. Wragg et al (2001) conducted a survey of a random sample of 1000 schools in order to investigate this process. They found in these schools that 88% of the eligible teachers applied; of these, 97% were awarded the bonus.…”
Section: The Prp Schemementioning
confidence: 99%
“…It is this difference that we capture here, so our results may underestimate the effect of the scheme. Wragg et al (2001) conducted a survey of a random sample of 1000 schools in order to investigate this process. They found in these schools that 88% of the eligible teachers applied; of these, 97% were awarded the bonus.…”
Section: The Prp Schemementioning
confidence: 99%
“…Bowman (2009) (Cutler and Waine, 1999;Chamberlin et al, 2002;Farrell and Morris, 2004;Richardson, 1999;Wragg et al, 2003). Waine (2000) gives an outline of the field with the British New Labour policy as a starting-point.…”
Section: Individual Performance-related Pay For School Teachersmentioning
confidence: 99%
“…The effects were somewhat smaller, but so too was the number of positive replies to that question. These estimates are consistent with those of early case studies by Wragg et al (2001), and by Mahoney et al (2003), who found modest effects of the new system in changing how teachers perform. However, what these early studies could not capture is the growth in the number of schools adopting the 'reformer' strategy.…”
supporting
confidence: 82%